The development of artificial intelligence and law in Taiwan - JSENG, Pin-Chieh (Vietnam national university, Hanoi, 2020)
I. Introduction. II. Legal Issues of Artificial Intelligence. A. Equality. B. Democracy. C. Freedom. D. Personality. E. Responsibility. III. Perception of Unmanned Vehicles. Technology Innovative Experimentation Act. A. The Concept of Unmanned Vehicles. B. Characteristics of UVTIEA. IV. Conclusion: From Private Cars to Mobility Services